Implementation of the Policy for Supervision and Control of Livestock Animals in Pasangkayu Regency - Rita Rita; Nuraisyah Ambo; Hafiz Ali Raza (PT. Multidisciplinary Press Indonesia, 2024)
This research is to determine the implementation of policies for monitoring and controlling livestock in Pasangkayu District, Pasangkayu Regency. The type of research used is descriptive qualitative. Data types use primary data and secondary data. Data collection techniques are carried out through observation, interviews, and documentation. The informant withdrawal technique uses purpose. The data analysis used is the Miles, Huberman, and Saldana model, namely data collection, data presentation, data condensation and drawing conclusions. Based on the results of the research conducted, the implementation of the policy for monitoring and controlling livestock in Pasangkayu District, Pasangkayu Regency, is relatively ineffective, there are still many violations committed by livestock owners. Several factors cause this regional regulation to be ineffective in its implementation because the agency given the authority no longer carries out supervision, control and outreach to people who own livestock. Apart from that, there are minimal resources prepared, be it financial resources, equipment resources. Another problem is the lack of strict sanctions given to livestock owners who violate the rules. There are no standard operational procedures for implementing livestock policies in the Pasangkayu District area.